CIÊNCIA ECONÔMICA - BRUM, ARGEMIRO L.; RONCATTO, DAIANA; PETRY, DEBORA C.; SAUGO, DIEGO A.; DIDOLICH, EVERTON F.; SILVA, GABRIELA M. D.; WALDOW, HEITOR; KUNZ, JULIANE; ZINGLER, KARINE D.; REIMANN, MARISA T.; FILHO, MAURICIO R. C.; MÜLLER, PATRÍCIA K.; et al. (Salão do Conhecimento, 2013)
Resumo